2020
DOI: 10.1186/s13578-020-00499-9
|View full text |Cite
|
Sign up to set email alerts
|

KLHL18 inhibits the proliferation, migration, and invasion of non-small cell lung cancer by inhibiting PI3K/PD-L1 axis activity

Abstract: Background The expression of Kelch-like protein 18 (KLHL18) in non-small cell lung cancer (NSCLC) is lower than that in normal lung tissue according to the Gene Expression Profiling Interactive Analysis database. KLHL18 is a BTB domain protein and binds cullin 3 (CUL3). However, whether this complex participates in ubiquitination-mediated protein degradation in NSCLC is unclear. Therefore, we aimed to investigate the role of KLHL18 in human NSCLC cells. Results We found that KLHL18 is downregulated in cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“… 19 More importantly, KLHL18, a BTB domain protein and binds CUL3, can suppress non-small cell lung cancer by reducing the activity of PI3K/PD-L1 axis. 37 Thus, we made a conclusion that CUL3/SPOP could degrade PD-L1 to suppress immune escape of ovarian cancer cells and promote the sensitivity of ovarian cancer cells to chemotherapy, suggestive of the critical roles of CUL3 and SPOP in ovarian cancer.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“… 19 More importantly, KLHL18, a BTB domain protein and binds CUL3, can suppress non-small cell lung cancer by reducing the activity of PI3K/PD-L1 axis. 37 Thus, we made a conclusion that CUL3/SPOP could degrade PD-L1 to suppress immune escape of ovarian cancer cells and promote the sensitivity of ovarian cancer cells to chemotherapy, suggestive of the critical roles of CUL3 and SPOP in ovarian cancer.…”
Section: Discussionmentioning
confidence: 73%
“…19 More importantly, KLHL18, a BTB domain protein and binds CUL3, can suppress nonsmall cell lung cancer by reducing the activity of PI3K/ PD-L1 axis. 37 Thus, we made a conclusion that CUL3/…”
Section: Discussionmentioning
confidence: 91%
“…PD-L1 as an important immune checkpoint protein could drive T-cell dysfunction and induce immunosuppression. Enhanced autophagy is related to the inhibition of PD-L1 expression in tumor cells. , Moreover, there is now a growing appreciation that the suppressed PI3K/AKT/mTOR pathway can decrease the expression of PD-L1 through promoting autophagy, thereby increasing the number of T cells and contributing to the tumor’s immunity activation. Therefore, the PD-L1 expression was immunohistochemically stained, and the CD4 + and CD8 + tumor-infiltrating lymphocytes (TILs) in tumor tissues were detected by immunohistochemistry and immunofluorescence assays to determine the impacts of CLQ platinum­(IV) complexes on tumor immunity. Results in Figure depicted that complex 5 remarkably suppressed the secretion of PD-L1 in tumor tissues to 20.5% of the blank group, which was also obviously lower than that of platinum­(II) drugs CDDP (44.9%, P < 0.001) and OLP (55.8%, P < 0.001).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In the present study, KLHL38 was found to promote activation of Akt and its downstream partners by promoting ubiquitin-dependent PTEN degradation. A previous study on KLHL18, another member of the KLHL family, demonstrated that the BTB domains in KLHL18 are critical for the ubiquitination of PI3Kp85α 23 . However, it was not possible here to identify which KLHL38 domains are involved in the PTEN ubiquitination process.…”
Section: Discussionmentioning
confidence: 99%